A Look Into the Past. Serbia 1965-91, part 1: The 1965 Reform - Paković, Zlatko (Serbia and Montenegro : Anрelizh, Bojan, 2003)
The when and whys of the failed processes of the country's democratization and decentralization. Was the disintegration of Yugoslavia already foreshadowed back at that time? From the 1960s onwards the conflict between modern and conservative, reform and anti-reform, centralist and federalist forces dominates the League of Communist of Serbia, and Serbian society as a whole. The anti-reform current wins the battle. The 1968 student protest and the Praxis group. A period crucial to understanding the processes that triggered the dissolution of the Yugoslav state and the accompanying wars.
Duration: 01:00:00
Keywords: Documentary films